Public university students' preferences for restrictionist or lenient immigration policies. (March 2021) - Sládková, Jana; Kim, Seokbeom; Cook, Kristin
Abstract: Few attempts have been made to examine the effects of perceived threats that immigrants pose to host society on young people's preferences for restrictionist or lenient immigration policies. Moreover, the existing literature is scarce on whether such perceived threats mediate the relationship between previously identified demographic antecedents such as gender, race or age and preferences for certain immigration policies. To address these gaps, this study examines direct and mediating effects of perceived economic, cultural and security threats on preferences for lenient or restrictionist immigration policies. Using a sample college students' survey data (N = 604) on their attitudes towards immigration, our findings of logistic regression analysis show that the three dimensions of perceived threat were all positively associated with preference for hardline immigration policies. In addition, regardless of inclusion of perceived threats in the logistic model, being Republican was a consistent positive predictor of the hardline immigration agenda, while female was a consistent negative one. Finally, the results of path analysis of Structural Equation Modeling indicate mediating effects of cultural threat on the relationships between political affiliation (Republican and Independent) and race (Latino) and support for hardline immigration policies.